Effects of Controlled Far‐Infrared Treatment on Granular Swelling and Rheological Properties of Crop Starches. (20th January 2020) - Guo, Baozhong; Wu, Jianyong; Hu, Xiuting; Luo, Shunjing; Wang, Haoqiang; Xu, Shunqian; Huang, Zhaohua; Liu, Chengmei
Abstract: Rheological properties of starch‐based foods influence their processability, mouthfeel, and shelf life and are considered to be primarily related to granular swelling of starches. In this work, four major crop starches (rice, maize, wheat, and potato) are treated by controlled far‐infrared ray (FIR) treatment to investigate the changes and correlations of swelling and rheological properties. The granular swelling of all starches is obviously decreased by FIR treatment. However, the changes in rheological properties by FIR treatment depend on sources of starches. FIR decreases the critical strain, flow point, and K value of rice and wheat starch gels, but increases those of potato starch gel. Moreover, the KG ′ and in‐shear structural recovery of potato starch gel are decreased by FIR, while those of rice and wheat starch gels are increased. Therefore, the rheological properties of crop starches are not determined by granular swelling. Nevertheless, the FIR still can be an effective physical treatment for starch modification. Abstract : In this work, four major crop starches (rice, maize, wheat, and potato) are treated by controlled far‐infrared ray (FIR) treatment to investigate the changes and correlations of swelling and rheological properties. The results indicate that rheological properties of crop starches are not determined by granular swelling, but the FIR treatment still can be an effective physical treatment for starch modification.